Acute intermittent porphyria: a disease with low penetrance and high heterogeneity - Lei, Jia-Jia; Li, Shuang; Dong, Bai-Xue; Yang, Jing; Ren, Yi (Frontiers in Genetics, 2024)
Acute intermittent porphyria (AIP) is caused by mutations in the gene encoding hydroxymethylbilane synthase (HMBS), a key enzyme in the heme biosynthesis pathway. AIP is an autosomal dominant disorder characterized by low penetrance and a highly heterogenous clinical presentation. The estimated prevalence of AIP is 5 -10 cases per 100,000 persons, with acute attacks manifesting in less than 1% of the at-risk population. This low frequency of attacks suggests significant roles for oligogenic inheritance and environmental factors in the pathogenesis of the disease. In recent years, identification of several modifier genes has advanced our understanding of the factors influencing AIP penetrance and disease severity. This review summarizes these factors including the impact of specific HMBS mutations, oligogenic inheritance, mitochondrial DNA copy number, age, sex, the influence of sex hormones, and the role of environmental factors. Further studies into the etiology of AIP disease penetrance should inform pathogenesis, potentially allowing for the development of more precise diagnostic and therapeutic approaches.